Поселение Затока-I («Гермонактова деревня») в Нижнем Поднестровье (характеристика материалов) - Бруяко, И.В.; Малюкевич, А.Е. (Материалы по археологии Северного Причерноморья, 2009)
The article is devoted to the examination of archaeological materials from the settlement Zatoka-I. The remains of this site are situated on the right bank of Dnester Lake, not far from the Black Sea shore. There are some dates to identify the settlement Zatoka-I with the “Village of Hermonacthos” of ancient written sources (Strabon). Accordingly to different finds (mainly pottery) we are able to determine chronology of this site in frames of the 4th (end 5th) the first third of the 3rd cc. B.C. (the first period) and the last third of the 3rd - the first quarter of the 2nd cc. B.C. (the second period).